2017
DOI: 10.1002/adom.201700164
|View full text |Cite
|
Sign up to set email alerts
|

All‐Angle Invisibility Cloaking of Contact Fingers on Solar Cells by Refractive Free‐Form Surfaces

Abstract: This work demonstrates a performance improvement of state‐of‐the‐art silicon solar cells by cloaking their metal contact fingers. The cloaking free‐form surfaces are fabricated on silicon heterojunction solar cells using direct laser writing of polymers and subsequent soft imprinting. Cloaking performance is determined experimentally by measuring spatially resolved and angle‐resolved current generation and the spectral response of the cell. The short‐circuit current density of the cell increases by 7.3%; its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…As a comparison, Ho et al showed a 3% increase in the EQE with increased incident angle using nanoparticle surface coatings . Schumann et al attained a 7.6% increase in the short circuit current using refractive surfaces . We show that the EQE and current output of the solar cell can be enhanced, both at normal incidence as well as over a wide angular range, by as much as 10% and 20%, respectively, the latter of which is critical for increasing total energy conversion in solar cells over the course of a day and across seasons.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…As a comparison, Ho et al showed a 3% increase in the EQE with increased incident angle using nanoparticle surface coatings . Schumann et al attained a 7.6% increase in the short circuit current using refractive surfaces . We show that the EQE and current output of the solar cell can be enhanced, both at normal incidence as well as over a wide angular range, by as much as 10% and 20%, respectively, the latter of which is critical for increasing total energy conversion in solar cells over the course of a day and across seasons.…”
Section: Introductionmentioning
confidence: 58%
“…A particularly attractive materials‐based approach is to engineer the encapsulation material (typically made from either polymer resins or glass), whereby specifically designed and fabricated optical structures manage the transmission of light to maximize delivery to the active regions of the cell. Examples include coatings, diffraction and diffuse layers, geometric optical structures, cloaking schemes, as well as light‐guiding mechanisms…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent development in optical engineering could significantly change the discussion, namely, the use of 3D surface contouring and/or refractive index grading of transparent polymers via direct laser writing to optically cloak the metallic lines—bending light around the electrodes and effectively making them invisible to the solar cell ( Figure 18 ). This strategy allows a majority of the photocurrent lost to shadowing to be regained in addition to providing some environmental encapsulation. When employed in carbon nanotube–silicon solar cells along with effective AR, this can limit optical losses to being solely those of the nanotube film absorption features which, as previously described, can be engineered to a minimum of just a few percent in the range of silicon's absorption.…”
Section: Improving Performancementioning
confidence: 99%
“…These include the use of lossy metals instead of PEC for the rear contact and back-reflector, power loss in the emitter region due to sheet resistance and increased surface recombination velocity. We do not explicitly consider shadowing loss of the front contacts given recent advances in broad-band, wide-angle cloaked-contacts [34][35][36][37] and interdigitated back contacts (IBC) [5,[30][31][32].…”
Section: Practical Considerationsmentioning
confidence: 99%
“…Accurate simulation of an IBC cell would require at least a 2D transport model for photo-generated charge carriers [33]. The second approach is the application of a dielectric coating over the contacts that effectively "cloaks" them by refracting nearly all incident sunlight "around" the metal fingers [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%